Whose Time? Which Rationality? Reflections on Empire, 1 Peter, and the "Common Era". Issue 3 (3rd September 2015) - Wan, Wei-Hsien
Abstract : The Roman imperial cults and the early Christians articulated different constructions of time, each offering its version of history built around a particular axis. The Augustan era inaugurated a transformation that reconfigured the imagination of time around the emperor and the ordo of statecraft. As a forerunner of later developments in the Christian tradition, the First Letter of Peter, on the other hand, anchored its vision of time in the life, death and resurrection of Jesus of Nazareth. Using this contrast as a launching point for reflection on social constructions of time, this paper examines the notion of a "Common Era" that has, in recent decades, gained widespread use in the academic practice. Despite its appearance as a more inclusive way of indicating "shared time", I argue that it functions, rather insidiously, to mask as universal a construct that is in fact culturally-specific and localized in the European Christian experience.